The 1998 floods and beyond : towards comprehensive food security in Bangladesh - Dorosh, Paul Anthony; Del Ninno, Carlo; Shahabuddin, Quazi; International Food Policy Research Institute (Dhaka : University Press, 2004)
Contributed articles.
"International Food Policy Research Institute."
Includes statistical tables.
Includes bibliographical references and index.
Keywords: Food supply -- Bangladesh; Food policy -- Bangladesh; Food industries and trade -- Bangladesh; Floods -- Bangladesh; Food supply -- Bangladesh -- Statistics